2006
DOI: 10.1007/s10832-006-7729-7
|View full text |Cite
|
Sign up to set email alerts
|

Structural and electrical properties of low resistance Pt/Pd/Au contact on p-GaN

Abstract: We have investigated electrical and structural properties of Pt/Pd/Au ohmic contact on p-type GaN:Mg (2.5 × 10 17 cm −3 ) using Auger electron spectroscopy (AES) and glancing angle x-ray diffraction (GXRD) analysis. It was shown that the specific contact resistivity improved with increasing annealing temperature. The annealing of the contact at 600 • C for 2 min in flowing N 2 atmosphere resulted in a specific contact resistivity of 3.1 × 10 −5 cm 2 . Both GXRD and AES depth profile results show that Ga 3 Pt 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…By means of this technique, we obtained that the sheet resistance equals to 53 kΩ and the contact resistivity equals to 2.7 mΩ cm 2 (averages obtained on 6 samples). These values are quite high for state-of-the art devices (for istance, ρ C = 31 µΩ cm 2 in [8]). However, we have chosen to carry out the study on these structures, because they showed enhanced degradation when submitted to thermal stress: in this way, we Original Paper have been able to achieve an accurate description of degradation kinetics.…”
Section: Resultsmentioning
confidence: 98%
“…By means of this technique, we obtained that the sheet resistance equals to 53 kΩ and the contact resistivity equals to 2.7 mΩ cm 2 (averages obtained on 6 samples). These values are quite high for state-of-the art devices (for istance, ρ C = 31 µΩ cm 2 in [8]). However, we have chosen to carry out the study on these structures, because they showed enhanced degradation when submitted to thermal stress: in this way, we Original Paper have been able to achieve an accurate description of degradation kinetics.…”
Section: Resultsmentioning
confidence: 98%
“…Generally, the epitaxial growth of III-nitrides has focused on the improvement of optical and crystal qualities of InGaN multi-quantum wells (MQWs) since they are used as active medium of AlInGaN-based laser diodes (LDs) as a lighting source for optical storage system and mobile display systems [1][2][3][4][5][6][7]. Recently, although the reliability of AlInGaN-based LDs has been drastically improved by the introduction of GaN substrate with low dislocation density, there are some reliability problems in the AlInGaN-based LD/LEDs [1].…”
Section: Introductionmentioning
confidence: 99%